Lost Floodplain Wetland Environments and Efforts to Restore Connectivity, Habitat, and Water Quality Settings on the Great Barrier Reef - Waltham, Nathan J.; Burrows, Damien; Wegscheidl, Carla; Buelow, Christina; Ronan, Mike; Connolly, Niall; Groves, Paul; Marie-Audas, Donna; Creighton, Colin; Sheaves, Marcus (Frontiers in Marine Science, 2019)
Managers are moving towards implementing large-scale coastal ecosystem restoration projects, however, many fail to achieve desired outcomes. Among the key reasons for this are a lack of integration with a whole-of-catchment approach, the scale of the project (temporal, spatial), the requirement for on-going costs for maintenance, lack of clear objectives, a focus on threats rather than services/values, funding cycles, engagement or change in stakeholders, and prioritization of project sites. Here we critically assess the outcomes of activities in three coastal wetland complexes positioned along the catchments of the Great Barrier Reef (GBR) lagoon, Australia, that have been subjected to restoration investment over a number of decades. Each floodplain has been modified by intensive agricultural production, heavy industry and mining infrastructure, urban/peri urban expansion, aquaculture development and infrastructure expansion. Most development has occurred in low-lying coastal floodplains, resulting in major hydrological modifications to the landscape. This has left the floodplain wetlands in a degraded and hydrologically modified state, with poor water quality (hypoxic, eutrophication, sedimentation, and persistent turbidity), loss of habitat, and disconnected because of flow hydraulic barriers, excessive aquatic plant growth, or establishment of invasive species. Successful GBR wetland ecosystem restoration and management must first include an understanding of what constitutes ‘success' and be underpinned by understanding of complex cause and effect pathways, with a focus on management of services and values. This approach should recognize these wetlands are still assets in a modified landscape. Suitable, long term, scientific knowledge is necessary to provide government and private companies with the confidence and comfort that their investment delivers dividend (environmental) returns.